Människor mötas, och ljuv musik uppstår i hjärtat: Kärlek, musik, berättelser, rituella tillfällen - Arvidsson, Alf (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1998)
In this article the author discusses how music is used for constructing concepts of love. In the analysis this is considered a complex interplay between music, experiences of love, narratives of love-experiences which offer models for romantic music, and arranged love-meetings where music is present as a means of ritualizing the event. The images of love present in the narratives or listeners to a radio request programme as well as the answers from a group of students to the question of which music they would choose for a meeting with their beloved, are concrete examples analyzed in the article.